Re-imagining the use of integrated assessment models from a social science perspective—lessons from the Sustainable Development Pathways (SDP) - Ariel Macaspac Hernandez; Sarah E Cornell; Dorothee Keppler; Vassilis Daioglou; Bjoern Soergel (Environmental Research Letters)
Socio-political factors in Integrated Assessment Models (IAMs), and their scenario narratives often lack transparency for policymakers and interdisciplinary scholars. As these tools increasingly support sustainable development goals, their assumptions and methodologies require scrutiny, particularly from social scientists. We address critiques of climate isolationism, overemphasis on technological transitions, and insufficient inter- and transdisciplinarity, advocating for robust interdisciplinary integration and clearer methodological transparency. Our recommendations stem from expert interviews and over 200 stakeholders across 30 countries from 2019 to 2024, emphasizing the need for cohesive theory and comprehensive social science engagement to refine these critical tools. Our main case study uses a new scenario set, the Sustainable Development Pathways (SDPs), that made substantial efforts to address social sciences critiques. The SDPs consist of both narratives and IAM-quantified target-seeking scenarios that are supported by social science concepts and theories to ensure not only theoretical coherence, but also their credibility among policymakers. As such tools are increasingly used to facilitate policies and actions for sustainability transformation, questions are raised about how they can effectively represent the complexities behind the current polycrisis that is marked by the climate crisis, biodiversity loss, economic inequality and social injustice. The paper concludes by reflecting on the remaining challenges and open questions related to the role of exogenous sociopolitical factors, the potential for scenarios to transcend political ideologies, and the need for ongoing adaptation of SDPs to reflect the dynamic global context. It calls for continued engagement and exploration of these issues to ensure the scientific representation of sustainable and equitable futures.